Learning tools development based on Technological, Pedagogical, and Content Knowledge (TPACK) - Susanti Susanti; Khusnul Safrina; Dwi Rizka Febriani; Rifaul Khairi (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
Research on the development of TPACK-based learning tools in this linear program aims to develop Lesson Plan (RPP), Learner Modules and Worksheets (LKPD). The lesson plans in this study were developed by following the steps of learning based on Discovery Learning and by adding the TPACK component. The module and LKPD in this study were developed by incorporating the TPACK element. The module in this study can be accessed in 2 ways, hardcopy and also an online module within play store. This study was designed using a 4D development design. The instrument used in this study was in form of validation sheet. The tools that have been developed in this study were validated by experts consisting of 2 lecturers of mathematics education study program, 1 mathematics teacher and 1 widiyaswara (Civil Servant Supervisor). The results showed that the Lesson Plan that had been developed had a legitimate level of validity, the Learner Module developed had a fairly valid level of validity and the Worksheet developed also had very good criteria.